2014
DOI: 10.1186/s12966-014-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an intervention aimed at reducing the intake of sugar-sweetened beverages in primary school children: a controlled trial

Abstract: BackgroundSince sugar-sweetened beverages (SSB) may contribute to the development of overweight in children, effective interventions to reduce their consumption are needed. Here we evaluated the effect of a combined school- and community-based intervention aimed at reducing children’s SSB consumption by promoting the intake of water. Favourable intervention effects on children’s SSB consumption were hypothesized.MethodsIn 2011-2012, a controlled trial was conducted among four primary schools, comprising 1288 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 60 publications
0
63
0
1
Order By: Relevance
“…Risk of bias across the 40 studies meta-analysed (in 38 existing articles) was generally medium to high, and unclear judgments were due to insufficient study details for all appraised domains; only four studies were judged to be of higher quality (48,55,63,73). The risk of bias for allocation concealment was high in 6 studies (16%) and unclear for 23 (61%) as a result of including nonrandomized interventions (40,46,50,60,62,66,70). A high risk of bias was found for outcome assessment in 8 studies (20%) as many results were not reported as being adjusted for confounders or attrition rates.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias across the 40 studies meta-analysed (in 38 existing articles) was generally medium to high, and unclear judgments were due to insufficient study details for all appraised domains; only four studies were judged to be of higher quality (48,55,63,73). The risk of bias for allocation concealment was high in 6 studies (16%) and unclear for 23 (61%) as a result of including nonrandomized interventions (40,46,50,60,62,66,70). A high risk of bias was found for outcome assessment in 8 studies (20%) as many results were not reported as being adjusted for confounders or attrition rates.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…We extracted data on socio-demographic features to identify the effects of interventions on health equity. All studies indicated the gender of participants at baseline; 8 studies were conducted only in females (37,39,58,59,62,63,70,74), one in a male sample (49), 11 in low-income populations (42,45,49,50,53,56,60,63,68,72,74), 15 studies reported a health condition at baseline (being overweight or obese and having metabolic-syndrome),14 studies reported race/ethnicity of participants (African-American, Native-Canadian, American-Indian, Hispanic, Caucasian). Three studies (41,43,51) analysed results by gender and one study reported economic costs of the intervention (46).…”
Section: Progress/equitymentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, several intervention studies have examined the effects of the replacement of sugary beverages’ consumption by the consumption of water, in which a reduction in total calories [9,20,21], positive behavioural changes and weight loss have been demonstrated [20]. Nevertheless, discouraging children from drinking sugary drinks and switching to water is challenging, considering the many physical and social environmental factors that may influence their choices.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to reduce SSB consumption include initiatives by major beverage companies to reduce the caloric content, taxation policies, nutritional counseling, and substituting with water or non-caloric sweeteners instead [9][10][11][12][13][14]. Although several investigators have demonstrated the effectiveness of education, in a meta-analysis of recent studies aimed at reducing SSB consumption, none included an educational intervention aimed specifically at children and devoted to awareness of sugar content in beverages [15].…”
Section: Introductionmentioning
confidence: 99%